Pengaruh Penerapan Model Pembelajaran Guided Note Taking (GNT) terhadap Hasil Belajar IPA Siswa - Opi Rahmah Hidayat; Yessy Fuji Utami (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to determine the effect of the application of the Guided Note Taking (GNT) learning model to the learning outcomes of science students in class VII in SMP Negeri 2 Lareh Sago Halaban District Academic Year 2017/2018. This type of research is an experiment. The population consists of class VII, amounting to 5 classes. Sampling is done randomly (random sampling). The selected sample is class VII.3 as the experimental class and class VII.5 as the control class. The instrument used as a data collection tool is a test. Data analysis techniques used t test, with acceptance criteria H1 if tcount> t table with α = 0.05. The results of data analysis obtained tcount = 2.88 and t table = 1.67, means tcount> t table so the hypothesis is accepted. In conclusion, there is a significant effect of the application of the Guided Note Taking (GNT) model to the learning outcomes of science students in class VII in SMP Negeri 2, Lareh Sago Halaban District. Keywords : Guided Note Taking (GNT), Learning Ourcomes, Student Learning